Development of Critical Thinking Essay Test Instrument and Prosocial Intention Questionnaire for Environmental Care in Students - Muhammad Ikhsan; Sri Atun; Fauji Agusta; Habibatul Unayah; Rusdiman Buhera; Oky Pamungkas; Muhamad Sarip; Patar Ariyanto Sitorus (Journal Evaluation in Education (JEE), 2025)
Purpose of the study: Assessment of students' critical thinking skills and environmental care attitudes is crucial for science learning. This research aims to develop an essay test instrument for critical thinking and a questionnaire for environmental care attitudes, evaluating their validity through expert assessments and trials. Methodology: Utilizing the Research and Development (R&D) model by Oriondo & Dallo-Antoio (1998), the study comprises three stages: test planning, trials, and validation. A random sampling technique was employed, involving 267 students. The critical thinking instrument consists of essay questions, while the environmental care attitudes are measured using a prosocial intentions questionnaire. Main Findings: Validity results indicate a high Aiken index of 0.96 for critical thinking essays and 1.0 for the environmental care questionnaire. Reliability estimates were 0.73 for critical thinking and 0.71 for environmental attitudes, both good. The difficulty level for the critical thinking instrument was classified as medium (0.68), while the environmental care instrument was deemed difficult (1.65). Limitations include focusing solely on science subjects, trials restricted to one area, and reliance on self-reports for environmental attitudes, which may introduce bias. Novelty/Originality of this study: The novelty of this study lies in integrating critical thinking assessment with environmental care attitudes, a rare approach in previous research. In conclusion, the developed instruments effectively measure students' critical thinking skills and environmental care attitudes in science education, particularly regarding global warming.